Chemerin-Derived Peptide Val66-Pro85 Is Effective in Limiting Methicillin-Resistant S. aureus Skin Infection - Zegar, Aneta; Godlewska, Urszula; Kozłowska-Chmielewska, Dorota; Majewski, Pawel; Zabel, Brian A.; Cichy, Joanna (Frontiers in Microbiology, 2021)
Chemerin-derived peptide Val66-Pro85 (p4) restricts growth of a variety of skin-associated bacteria, including methicillin-resistant S. aureus (MRSA). To better understand the antimicrobial potential of chemerin peptide, we compared p4 activity against MRSA in vitro to cathelicidin LL37, one of the key endogenous peptides implicated in controlling the growth of S. aureus. The efficacy of p4 was also validated in relevant experimental models of skin pathology, such as topical skin infection with community acquired MRSA, and in the context of skin inflammatory diseases commonly associated with colonization with S. aureus, such as atopic dermatitis (AD). We show that p4 collaborates additively with LL37 in inhibiting the growth of S. aureus, including MRSA, and that p4 is effective in vivo in reducing MRSA burden. P4 was also effective in reducing levels of skin infiltrating leukocytes in S. aureus-infected AD-like skin. Taken together, our data suggest that p4 is effective in limiting S. aureus and, in particular, MRSA skin infection.